A comprehensive analysis of piezoelectric energy harvesting from bridge vibrations. (22nd December 2022) - Zhang, Zhiwei; Xiang, Hongjun; Tang, Lihua; Yang, Weiqing
Abstract: Piezoelectric energy harvesting from bridge vibrations has the potential to power wireless sensors used for bridge health monitoring. Often, it is necessary to store the harvested energy before it could be used to power the sensor intermittently. However, the behavior of the piezoelectric energy harvester (PEH) with nonlinear interface circuits for energy extraction and storage subject to realistic bridge vibrations has not been fully understood. This work performs a comprehensive analysis on the performance of the PEH subject to the measured railway bridge vibrations and compares the energy stored on a capacitor using four different interface circuits. Firstly, the dynamic characteristics of the railway bridge is analyzed. A cantilevered PEH is then designed and fabricated based on the dynamic characteristics of the bridge. Subsequently, four realistic energy extraction and storage interface circuits, namely, the standard energy harvesting (SEH), synchronized charge extraction (SCE), parallel synchronized switch harvesting on inductor (P-SSHI) and series SSHI (S-SSHI) circuits, are evaluated and compared when the PEH subject to the measured bridge vibrations. The influence of the storage capacitance and the 1st short-circuit natural frequency of the PEH on the stored energy with these four circuits is then discussed. An optimal storage capacitance exists in the systems based on SEH, P-SSHI and S-SSHI circuits. The system based on P-SSHI circuit has the highest efficiency on energy storage. This work provides a technical framework to develop the realistic energy harvesting and storage system for realization of self-powered bridge condition monitoring.